The Effect of Organizational Culture, Work Environment and Work Motivation on Employee Performance Mediated by Job Satisfaction in Employees at Bank Syariah Indonesia (BSI) Malang City Branch, Indonesia - Lydia Adilla Perdana; Aniek Rumijati; Mursidi Mursidi (urn:multiple://2988-7828multiple.v3i84)
This study aims to analyze the influence of organizational culture, work environment, and work motivation on employee performance through job satisfaction at Bank BSI Malang City Branch. The research sample consisted of 115 employees working in 8 branch office units that met certain criteria. The research data were collected through online questionnaires using Google Form and analyzed using the Smart PLS statistical method. The results of the study indicate that organizational culture has a significant positive effect on employee performance, as well as a positive effect on employee job satisfaction. The work environment was found to have a significant effect on employee job satisfaction, although it did not have a significant effect on employee performance. Work motivation did not have a significant effect on employee performance or job satisfaction. In addition, job satisfaction was shown to mediate the influence of organizational culture and work environment on employee performance. These findings indicate that good organizational culture management and a supportive work environment are very important in increasing job satisfaction, which in turn can contribute to improving employee performance. The results of this study provide useful insights for Bank BSI management in developing strategies to improve employee performance through improving organizational culture and a more conducive work environment.